(untitled) (Sahel Journal of Life Sciences FUDMA, 2026)
This study evaluated the biochemical composition and oxidative stability of garlic-fortified Silver Catfish (Chrysichthys nigrodigitatus) subjected to hot smoking. Fresh, non-fortified hot-smoked and garlic-fortified hot-smoked samples were analysed for proximate composition, nutrient-energy contribution, mineral content, lipid oxidation indices and correlation between proximate and mineral parameters. Moisture content was highest in fresh fish (77.03 ± 0.37%) but declined significantly after smoking to 9.65 ± 0.22% and 9.27 ± 0.15% in non-fortified and garlic-fortified samples respectively. Crude protein increased markedly, reaching the highest value in garlic-fortified fish (53.61 ± 0.60%), while crude fat and ash also increased following smoking. Energy value rose substantially from about 372 kJ/100 g in fresh samples to over 1200 kJ/100 g in smoked products, with protein energy contribution exceeding 58% in fortified samples. Mineral concentrations also increased after processing; for example, calcium rose from 18.6 ± 1.5 mg/100 g in fresh fish to 152.7 ± 6.1 mg/100 g in garlic-fortified samples, while potassium increased from 278.6 ± 10.5 mg/100 g to 533.4 ± 18.2 mg/100 g. Garlic fortification improved oxidative stability, as indicated by a higher iodine value (6.57%) and lower peroxide and thiobarbituric acid values compared with non-fortified smoked fish. Strong positive correlations (r ≈ 0.98–1.00) were observed between proximate and mineral parameters in smoked samples. The results demonstrate that garlic fortification enhances the nutritional quality and oxidative stability of hot-smoked C. nigrodigitatus.